Ken Yeang bioclimatic skyscrapers - Pidgeon, Monica (New York : Insight Media (distributor), 1994)
About professor Ken Yeang who is internationally renowned as the'father' of the'sustainable bioclimatic building'. His bioclimatic buildings extended to low-rise high density and sub-grade structures. Ken Yeang's architecture is based on his theoretical ecological studies published in The Green Skyscrapers
Title from container
Speaker: Ken Yeang
DVD format
Keywords: Yeang, Ken, -- 1948-; Skyscrapers; Skyscrapers -- Designs and plans; Architecture and climate; Architecture and energy conservation; Architecture -- Environmental aspects